REPRESENTASI PEREMPUAN DALAM FILM MARLINA SI PEMBUNUH DALAM EMPAT BABAK - Astawan, Putu Nala Parisudani; Sugiarica Joni, I Dewa Ayu; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2019)
ABSTRACT Marlina the Murderer in Four Acts, is one of the films that describes women's resistance to fighting negative stereotypes circulating in the community. It’s still strong patriarchal culture caused women to be depicted as weak and number two. However, women come up from adversity because women have a strong soul. This research uses Roland Barthes's semiotic analysis by looking for denotative meanings, connotative meanings and myths in analyzing the signs in films that represent women in this film. The results show that in the film Marlina the Murderer in Four Acts show the signs that represent women, that women, even though they are considered as the second class are able to show their strong side and can fight, women also have the courage to voice what they want and showing women still need protection. Keywords: Film, Women, Representation,Semiotics